A Study on Steel-Concrete-Steel Wall to Resist Perforation from Rigid Projectile Impact. (6th September 2021) - Han, Pengfei; Liu, Jingbo; Fei, Bigang; Wang, Fei
Abstract : A calculation method of SCS wall which is used in the third generation of nuclear power plants to resist perforation from rigid projectile based on energy method is proposed in this paper. The energy is divided into four parts including the energy dissipated by front steel plate, concrete, back steel plate, and tie bars. The method accounts for the perforation of the concrete and steel plates separately and accounts for the interaction between them, and a practical antiperforation calculation formula of SCS wall with tie bars is given. The most formular results are close to the test results and the FEM results with a deviation less than 10%, which shows that the calculation formula given in this paper is reasonable and credible to effectively evaluate the perforation failure of the SCS wall and carry out a relevant design. The energy dissipated by the steel plate is much larger than that of the tie bars through a comparative analysis of dissipated energy. The effects of various factors on perforation velocity are analyzed according to finite element calculation results, which can be roughly divided into three categories: the influence of the thickness of steel plate and distance of tie bar is the largest effect, followed by that of yield strength of steel plate, yield strength of tie bar and diameter of tie bar, and that of compressive strength of concrete is the smallest effect.